An analysis on the mastery of uppercase and lowercase letters in nouns among non-native speaker students - Subramaniam, Vijayaletchumy; Nagasundram, Usha; Yaakob, Nur Azuwan (The Joss Group, 2023)
A students skill incontructing outstanding grammaticalwriting starts from the skill of writing a sentence mechanically as well as theability to revise and refine paragraphs in the aspect of spellings, correct punctuation, the use of remuneration, appropriate utilization of words and the structure of sentences. This study focuses on mastering the use of uppercase and lowercase letters in common nouns and proper nouns among SJKT students.The respondents were 55 students of Year 5 from SekolahJenisKebangsaan Tamil Kajang.This study is based on a qualitative approach. In order to acquire data, researcher usedtext analysis, observations, and interviews. Data were analysed using Corder Language Error Analysis (1981). Findings showed that97of uppercase errors in proper nouns and the students are still less familiar with the common nouns as a second language speaker of Malay. Misconceptions in common nouns and proper nouns tend to use the wrong letters in writing.Therefore, all language users are advised to emphasize the proper usage of common and proper nouns to construct grammar sentences free of mechanical error.